Chronic heat stress facilitates lipoprotein lipase expression and triglyceride biosynthesis in the adipose tissue of growing broiler chickens - Yukako Tokutake; Takashi Miyazaki; Chinatsu Abe; Md. Rezwanul Habib; Shinichi Yonekura; Kan Sato (Scientific Reports)
Abstract Exposure to chronic heat stress not only reduces body weight gain in growing broilers, but also enhances fat deposition. To elucidate this effect, numerous studies have investigated the changes in the liver, the primary site of de novo fat synthesis in avian species, and a marked increase in fat accumulation has been observed under chronic heat stress. However, the impact of heat stress on adipose tissue remains largely unclear. To investigate alterations in adipose tissue following heat-exposure, we reared growing broilers in a high-temperature environment (32 °C) for 14 d. Despite the decreased feed intake, the ratio of abdominal fat to body weight in the heat-exposed group remained comparable to that in the control group. Furthermore, the heat-exposed group exhibited a marked decrease in plasma free fatty acid concentrations. Transcriptome analysis of abdominal fat from heat-exposed and control groups indicated 459 differentially expressed genes. In the heat-exposed group, genes associated with lipid synthesis showed increased expression in the adipose tissue. Heat stimulation induced the expression of the lipoprotein lipase gene in cultured primary adipocytes. These results suggest that chronic heat exposure promotes lipoprotein lipase expression and triglyceride biosynthesis in the adipose tissue of growing broilers.